Interview with Professor Om Gurung - Khattri, Man Bahadur; Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2021)
Professor Om Gurung is a senior anthropologist, an influencing intellectual, and a prominent public leader in Nepal. He served Tribhuvan University as a professor of anthropology for 36 years and headed the Central Department of Sociology/Anthropology for 13 years. Professor Gurung did his M. A. in History from Tribhuvan University in 1975, M. A. in anthropology from the University of Poona in 1980, and Ph. D. in Anthropology from Cornell University of Ithaca, New York in 1996. He is one of the founding members of the Central Department of Sociology/Anthropology at Tribhuvan University of Nepal. He has served as a visiting professor at the University of Wisconsin-Madison, Liverpool John Moores University in the UK, Lille University in France, and the University of Sichuan in China. He is a visiting research fellow at the University of Bergen, Norway, and a guest lecturer at Cornell University, Ithaca, New York, Oxford University, UK, China Institute of New School University, New York, the University of Mons, Belgium, the University of Heidelberg, Germany and Chinese University in Hong Kong. Professor Gurung was heavily engaged in various social, professional, and political organizations. He has made substantial scholarly and social contributions to the understanding of social and political issues of Nepal. As a promising intellectual leader of ethnic rights and politics of social inclusion in Nepal, he raised socio-political awareness among indigenous peoples of Nepal and mobilized them to assert their ethnic identity and cultural rights. He has a deep commitment to the development of anthropology and Nepali people.